Etnobotani Serai Wangi (Cymbopogon nardus (L.) Rendle) Desa Batang Kulur Kecamatan Kelumpang Barat Kotabaru - Puteri Nadirah; Meyninda Destiara; Istiqamah Istiqamah (Tadris Biologi, Tadris Fisika and Tadris Kimia, Universitas Islam Negeri Antasari, 2022)
This study aims to describe the ethnobotanical study of the citronella plant (Cymbopogon nardus (L.) Rendle) for the people of Batang Kulur Village, Kelumpang Barat District, and to describe the validity of the pocket book on the ethnobotany study of the citronella plant (Cymbopogon nardus (L.) Rendle) for the Batang village community. Kulur District of West Kelumpang. This research is a field research with a qualitative descriptive research approach. Sources of research data are respondents, informants, and the results of the documentation. Data collection techniques were carried out by observation, interviews and documentation. The results of the study were developed into a pocket book using R&D research with the Tessmer 1998 formative evaluation model. Based on the results of data analysis, it was found that the botanical study of citronella (Cymbopogon nardus (L.) Rendle) has perennial terna habitus, root system of short rhizomes, and single leaves that have a distinctive odor. Ethnosocioanthropology studies are used as complementary materials in traditional Banjar Betimung activities in the local community. Ethnoeconomic studies of citronella leaves are traded for the basic ingredients of producing essential oils for making massage oil. Ethnopharmacology studies processed traditional ingredients as a treatment for aches and pains. The ethnoecological study of citronella is very easy to plant by separating the saplings of the plant.